INTERMEDILYSIN AS POTENT VIRULENCE FACTOR IN ORAL COMMENSAL BACTERIUM STREPTOCOCCUS INTERMEDIUS - Susilowati, Heni (2013)
Streptococcus intermedius is commensal bacterium which colonize in mouth, gastrointestinal, and genitourinary tracts. Despite its less significance in the formation of dental plaque, this species also can be found in periodontal abscess and deep infections. It is interesting to be noted that this bacterium is closely related to the spread of oral origin infection into other parts of the body since its presentation as single colony grown from periodontal, brain, and liver abscess isolates. Although has been classified as commensal bacterium, this species is able to induce biological change on host cells. Virulence factors have been recognized to be produced by S. intermedius; one of those molecules is intermedilysin (ILY). Intermedilysin is member of cholesterol-dependent cytolysin produced by S. intermedius strain from abscess isolate. The toxin binds to human CD59 as the only membrane receptor responsible for the binding between ILY and human cells. Because of human specification of ILY, this toxin is accounted as key factor for bacterial invasion into host cells. Molecular and cellular changes have been identified as host cell responses to ILY exposure. Human red blood cells have been hemolyzed and generated irreversible membrane pore under ILY treatment. In addition, bile duct cells, hepatocytes, and polymorphonuclear cells also demonstrated irreversible nuclear and cell morphology destruction caused by ILY. It was confirmed that ILY is able to induce inflammation, immune responses, and cell death mechanisms on exposed cells. It is concluded that ILY plays significant role in molecular and cellular destruction caused by S. intermedius infection.